Impact of Short and Moderate Rest Intervals on the Acute Immunometabolic Response to Exhaustive Strength Exercise: Part II - Gerosa-Neto, Jose [UNESP]; Rossi, Fabrício E. [UNESP]; Campos, Eduardo Z. [UNESP]; Antunes, Barbara M.M. [UNESP]; Cholewa, Jason M.; Lira, Fabio S. [UNESP] (Wolters Kluwer, 2016)
Gerosa-Neto, J, Rossi, FE, Campos, EZ, Antunes, BMM, Cholewa, JM, and Lira, FS. Impact of short and moderate rest intervals on the acute immunometabolic response to exhaustive strength exercise: Part II. J Strength Cond Res 30(6): 1570-1576, 2016 - The purpose of this study was to investigate the influence of short and moderate recovery intervals during heavy strength exercise on performance, inflammatory, and metabolic responses in recreational weightlifters. Eight healthy subjects (age 24.6 ± 4.1 years) performed 2 randomized sequences with different rest intervals: short 90% of 1RM and 30 seconds rest allowed between sets; moderate 90% of 1RM and 90 seconds rest allowed between sets. All sequences of exercises were performed over 4 sets until movement failure in the squat and bench press exercises, respectively. Glucose, TNF-α, IL-6, IL-10, IL-10/TNF-α ratio, and nonester fatty acid concentrations were assessed at the baseline, immediately postexercise, post-15 and post-30 minutes. We observed a statistically significant decrease after 30 seconds on maximum number of repetitions (p 0.003) and total weight lifted (p 0.006) after the bench press, and there was a marginal decrease in the squat (p 0.055). The glucose concentrations showed a significant increase post-15 minutes in the 30-second condition (pre-exercise 86.1 ± 9.1, immediately 85.3 ± 8.2, post-15 97.0 ± 9.0, post-30 87.1 ± 5.3 mg/dl; p 0.015); on the other hand, IL-10 increased post-30 minutes in the 90-second condition (pre-exercise 18.2 ± 12.7, immediately 16.4 ± 10.7, post-15 16.8 ± 12.2, post-30 35.0 ± 13.1 pg/ml; p < 0.001). In addition, the 90-second condition showed anti-inflammatory effects (as indicated by IL-10/TNF-α ratio: pre-exercise 1.08 ± 1.32, immediately 1.23 ± 1.20, post-15 1.15 ± 1.14, post-30 2.48 ± 2.07; p 0.020) compared with the 30-second condition (pre-exercise 1.30 ± 2.04, immediately 0.99 ± 1.27, post-15 1.23 ± 1.82, post-30 1.28 ± 1.28; p 0.635). Thus, we concluded that a moderate interval of recovery (90 seconds) during heavy strength exercise allowed higher workload, IL-10 levels, and IL-10/TNF-α ratio in recreational weightlifters.
Keywords: inflammation; interval of recovery; metabolism